PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAPKINERJA STAF DAN TENAGA AHLI DI FRAKSI PKS DPR RI - Ero Sukana (NIAGARA Scientific Journal, 2023)
This research is intended as a concept for the application of the Human Resource Management Science function and also to reveal how much influence motivation has on work discipline and its impact on the performance of staff and experts in the F-PKS DPR RI. This research is a quantitative study using ex post facto design. The research data was taken with a questionnaire instrument which was filled by 173 samples determined by proportionate random sampling technique. The research data were analyzed by structural equation modeling through the Amos program. The results showed that: (1) There was an influence between work motivation and the work discipline of the staff and experts of the DPR RI F-PKS, (2) There was an influence between work motivation on the performance of the staff and experts of the DPR RI F-PKS, (3) There was the influence between work discipline on the performance of the staff and experts of the DPR RI F-PKS, and (4) There is an indirect effect between work motivation on the performance of the staff and experts of the DPR RI F-PKS through the mediation of work discipline